POTENSI ENERGI LISTRIK DAN TINGKAT KEASAMAN PADA BUAH JERUK NIPIS DAN BELIMBING WULUH - Naurah Rizki Pujiarini; Sudarti Sudarti (JFT : Jurnal Fisika dan Terapannya, 2021)
Energy in general is an activity or effort or work that can be done by certain forces such as electricity, heat, gravity, mechanics, chemistry and so on. The composition of Indonesia's energy currently derived from petroleum by 52.50%, amounting to 19.04% of natural gas, coal amounted to 21.52%, water by 3.73%, geothermal by 3.0%, and new energy by 0.2%. Electrolysis is an example of an alternative energy source. It uses an electrolyte solution to produce electricity, which is a solution capable of generating electricity. The solution usually comes from acidic fruits such as starfruit and lime. The study aims to know the potential for electrical energy that is generated, to know the intensity of the voltage that is generated, to know the current of acidity and to know the acidity of the acidification. This type of study is a quantitative study with the research method used, which is a method of experimentation. From this research, the results show that the starfruit solution has a pH of 0.40 with a voltage of 0,9 V; 1.7 V; 2.2 V and produces an electric current of 0.03 mA; 0.15 mA; 0.58 mA. The resulting lime solution has a pH of 1,39 with a voltage of 1 V; 1.8 V; 2.6 V and produces an electric current of 0.15 mA; 0.38 mA; 0.61 mA. Based on this research, it can be seen that starfruit and lime can be used as an electrolyte solution to produce electrical energy.